EFEKTIVITAS SUPERVISI KEPALA MADRASAH TERHADAP KUALITAS PEMBELAJARAN DI MIS SANANA - MARIA MARIA (ABDUSSALAM: Jurnal Pendidikan Dan Kebudayaan Islam, 2025)
This study aims to analyze the effectiveness of the headmaster's supervision on the quality of teaching at MIS Sanana. The research method used was qualitative, employing observation, interviews, and document studies for data collection. The results show that the headmaster's supervision was conducted in a structured manner, although teacher participation in the supervision planning process was limited. The implementation of supervision improved from the odd to the even semester, with classroom observation being the main technique. The impact of supervision was observed in the improvement of lesson planning quality, the use of active teaching methods, and student learning outcomes. However, challenges such as the headmaster's administrative burden and resistance from some senior teachers remained. This study highlights the need for more participatory, innovative, and technology-based supervision to enhance the quality of education in madrasahs.